Kino jidysz na ziemiach polskich do wybuchu drugiej wojny światowej - konteksty społeczno-polityczne i kulturowe - Mazur, Daria (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Yiddish Cinema in the Prewar Polish Lands: The Socio-political and Cultural Contexts The article is an attempt to consider the impact of social-political contexts on Yiddish cinema in Poland before the outbreak of the Second World War. It also analyses the influence of cultural and ideological tendencies represented by the diaspora in Poland: traditional – related to Judaism and Yiddish language; Zionist – trying to resurrect Israel and appealing to Hebrew as the language of the Jews; Bund – a left wing party that supported a secular Yiddish culture and opposed Zionism, as well as the assimilation of Polish culture and language.